Penerapan Merdeka Belajar Materi Pkn Pada Karakter Profil Pelajar Pancasila - Anggraeni, Levina; Purnomo, Heru (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research was conducted to determine the teacher’s role in shaping character education in Cibendung 02 Public Elementary School. The method used in this study was using qualitative methods. The sources of this research are students, class teachers, school principals, and also the surrounding community. Retrieval of data used is by interview, observation, and documentation. The techniques used in data collection consist of searching for data, presenting data, and the last is drawing conclusions. The results obtained from this study are that teachers have maximized the learning of Pancasila character education through other learning subjects. The teacher also directly applies examples of Pancasila student profile characters that students must have in their usual learning activities. For example, mutual cooperation activities in carrying out school cleaning activities so that they are completed quickly. The importance of growing the character of the Pancasila student profile is very important. Therefore, every school must instill the character profile of Pancasila students in each of their students, in order to form good character for this nation’s generation.